Prediction of Low Back Pain among School‑aged Adolescents using Parental Sociodemographic Variables in a Nigerian City (Nigerian Journal of Health Sciences, 2023)
Background: Low back pain (LBP) is the most prevalent musculoskeletal disorder among adults, but how parental sociodemographic factors associated with the prevalence of LBP among adolescents is still under investigation.Materials and Methods: Eight schools were selected randomly; from each school, 100 students were consecutively selected amounting to 800 participants for the study. LBP questionnaire from a study of Chiwaridzo and Naidoo was adopted for the research. The Likert scale questionnaire was administered to each participant and collected as soon as it was completed. Descriptive and inferential statistics were used to analyse the data. Alpha level was set at 0.05.Results: The results showed that 710 questionnaires, which were 88.7% of the total, were analysable. More than 46% of the participants recorded LBP in the last 1 year. There was significant association between occurrence of LBP and each of family history of LBP (χ2 = 13.357, P = 0.000), fathers’ occupation (χ2 = 13.357, P = 0.000) and education (χ2 = 13.357, P = 0.000); mothers’ occupation (χ2 = 13.357, P = 0.000)and education (χ2 = 13.357, P = 0.000). Prediction equation for the occurrence of LBP is: Y = K + B (Occupation) + C (Education) + D (LBP in the family). The r2 value was 0.473 interpreting that the percentage contribution of these factors to the prediction of LBP among adolescents was 47.3%.Conclusion: The study showed that prevalence of pain at low back was 46% among 10–14 years’ adolescents. Some parental sociodemographic variables may contribute to the occurrence of LBP among adolescents.